Prebiotic Activity of Plants from Cucurbitaceae Family and In Vitro Fermentation by Gut Microbiota - Ab Azid, Saffanah Mohd; Wichienchot, Santad; Wan Ishak, Wan Rosli; Safuan, Sabreena (Jurnal Gizi dan Pangan, 2024)
This study aims to examine the effect of Freeze-Dried Pumpkin Powder (FDPP), Freeze-Dried Winter Melon Powder (FDWMP), Freeze-Dried Rock Melon Powder (FDRMP), inulin, and D glucose on prebiotic activity score by in vitro fermentation. We also elucidate the changes in bacterial populations through batch culture fermentation using fecal samples from 5 healthy volunteers and In vitro fecal fermentation using batch culture and analyses of Short-Chain Fatty Acids (SCFAs). The growth of Bifidobacterium has significantly increased from 0 (8.90±0.05 log10 cells/mL) and 72h (8.83±0.14 log10 cells/mL) for D glucose and FDWMP (8.75±0.07 log10 cells/mL (0h) and 8.87±0.12 log10 cells/mL (72h)). However, the increase in population was not significant for inulin (9.15±0.06 log10 cells/mL), FDPP (9.04±0.12 log10 cells/mL), and FDRMP (8.67±0.08 log10 cells/mL). The number of Lactobacili significantly increased at 6h for FDPP (9.11±0.07 log10 cells/mL) and 24h for FDWMP (8.88±0.07 log10 cells/mL) and FDRMP (8.80±0.09 log10 cells/mL). Acetic acid was detected in all samples, and the concentration increased in all vessels at any given time except for the FDWMP fermentation, which decreased after 0h and increased after 6h. Overall, FDWMP has increased the probiotic growth of L. plantarum TISTR 1465 and exhibit the highest prebiotic index. As a result, it is suggested that the FDWMP be potentially used as a healthy raw material in developing varieties of functional prebiotic food products.